Pengaruh Current Ratio, Total Asset Turnover, Return on Equity dan Net Profit Margin terhadap Pertumbuhan Laba: (Studi Empiris pada Perusahaan Sektor Infrastruktur yang Terdaftar di Bursa Efek Indonesia Periode 2019 - 2023) - Nur Rachmania; Retno Fuji Oktaviani (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The purpose of this research is to examine the influence of Current Ratio, Total Asset Turnover, Return on Equity, and Net Profit Margin on Profit Growth. With a sample of Infrastructure Sector Companies for the 2019 - 2023 period, there were 79 companies and 8 companies were used as research samples using purposive sampling as the sampling technique. This research was carried out using multiple linear regression methods through data and hypothesis testing and using the Statistical Package for the Social Science program version 29 and Microsoft Excel 2019. The results of the research show that the Current Ratio and Total Asset Turnover have a significant effect on Profit Growth, while Return on Equity, and Net Profit Margin does not have a significant effect on Profit Growth.